Instrumentos utilizados para medir el compromiso laboral de los profesionales de enfermería (2024)
This research aims to describe the state of scientific knowledge about the instruments used in research to measure the work engagement of nursing professionals from 2018 to 2023. Method: The present study corresponds to a narrative review, each of the stages proposed by Whittemore & Knafl were taken into account. The search for articles was carried out in the databases: PubMed, Nursing and Ovid, Scielo, Lilacs, BVS, ScienceDirect through the Learning and Research Resources Center (CRAI) of the Antonio Nariño University